Volunteer Tourism and Host Community (International Journal of Scientific Research and Management (IJSRM), 2014)
The paper examines the status of volunteer tourism by providing an analysis of its conceptualization, development, cross-cultural misunderstanding and impacts on host society. Findings indicate the requirement of sustainable approach in order to maximize positive and minimize negative impacts on community. Existence of cross-cultural misunderstanding in volunteer tourism to be addressed adequately, research related to influences on host should be initiated and focused for development of impact measurement tools are some of the key findings of this paper.